2019
DOI: 10.1111/geb.13028
|View full text |Cite
|
Sign up to set email alerts
|

Grazing intensity significantly changes the C : N : P stoichiometry in grassland ecosystems

Abstract: AimLivestock grazing can alter carbon (C), nitrogen (N) and phosphorus (P) cycles, thereby affecting the C : N : P stoichiometry in grasslands. In this study, we aimed to examine mechanisms underlying the impacts of grazing on grassland C : N : P stoichiometry, focusing on belowground processes and their linkages with aboveground vegetation properties.LocationGlobal.Time period1900–2018.Major taxa studiedGrassland ecosystems.MethodsWe conducted a meta‐analysis based on 129 published studies to synthesize the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 45 publications
4
51
1
1
Order By: Relevance
“…Plant C concentration significantly reduced with grazing intensity in this study, while previous studies found plant C concentration had no significant response to grazing intensity (Ding, Gong, Wang, Wu, & Liu, 2012;Liang et al, 2019). Grazing intensity is a critical factor to regulate plant C dynamic (He et al, 2019). Compared with Liang et al (2019)'s study, higher grazing intensity had stronger damage to plant stems and leaves in this study, which could decrease accumulation of organic matter.…”
Section: Effect Of Grazing On Plant C N and Pcontrasting
confidence: 69%
See 1 more Smart Citation
“…Plant C concentration significantly reduced with grazing intensity in this study, while previous studies found plant C concentration had no significant response to grazing intensity (Ding, Gong, Wang, Wu, & Liu, 2012;Liang et al, 2019). Grazing intensity is a critical factor to regulate plant C dynamic (He et al, 2019). Compared with Liang et al (2019)'s study, higher grazing intensity had stronger damage to plant stems and leaves in this study, which could decrease accumulation of organic matter.…”
Section: Effect Of Grazing On Plant C N and Pcontrasting
confidence: 69%
“…The acceleration of soil nutrient cycling might provide enough N and P for plant growth. However, He et al (2019) reported that plant N/P ratio decreased with grazing intensity. These inconsistent results showed that plant N/P ratio might be an uncertain indicator of plant growth limitations in grazing grasslands, depending on grazing intensity and time.…”
Section: Effect Of Grazing On Plant C N and Pmentioning
confidence: 98%
“…The results revealed that grazing decreased P and N in the topsoil but did not influence other chemical properties such as pH, K, and the C:N ratio. The decrease in nitrogen due to grazing is a common phenomenon in heavily grazed grasslands (Han et al, 2008;He et al, 2019). Under low grazing intensities, the concentration of N in soils is usually unaffected due to the balance between N removal and N returned.…”
Section: Effect Of Drought and Grazing On Soil Propertiesmentioning
confidence: 99%
“…The only study we found that reported on P showed the P response to grazing is dependent on mean annual precipitation. It was shown that grazing reduces soil P when precipitation is lower than 400 mm but increases when it higher (He et al, 2019).…”
Section: Effect Of Drought and Grazing On Soil Propertiesmentioning
confidence: 99%
“…In addition, many previous studies have demonstrated that heavy grazing reduced plant diversity, biomass and soil organic carbon (SOC) content in alpine grassland (Dlamini et al 2016;Sun et al 2011;Sun et al 2018), and moderate grazing might help balance species diversity protection and biomass production (Li et al 2011). However, despite of these effects, the magnitude of grazing effects on alpine grassland varies due to the difference in grazing regime, grazing intensity, grazing duration, grassland types and environmental factors (He et al 2020;Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%